KEBIJAKAN PENGEMBANGAN PERMUKIMAN VERTIKAL DI PROVINSI DKI JAKARTA - Budiana Setiawan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2013)
The percentage of green open space (RTH) in Jakarta is only 9.6%. It is very lower than the minimum limit which be set by the World Health Organization (WHO), which is 30% of total area of a city. One cause of the least of remaining green open space in Jakarta is the fast growing of settlements. To prevent green open space in Jakarta is not diminished, Jakarta Provincial Government needs to change the strategy of development of settlements from horizontal to vertical. Vertical settlement is shaped in flats or apartments. Flats or apartments are the right alternative to answer the high demand of land for settlement on one side and still be able to maintain the integrity of the vast green open space on the other side. Despite this effort to realize the vertical settlements are blocked by three factors, i.e.: society, developer, and the Provincial Government of Jakarta. To overcome these problems, there are three factors to consider in determining government policy, namely: discourse / narratives, politic interest, and actors / network.